PENINGKATAN KAPASITAS GUDANG DENGAN REDESIGN LAYOUT MENGGUNAKAN METODE SHARED STORAGE - irawan noor (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2018)
Planning of layout warehouse useful to help production to flow ofproduct will be distributed. Warehouse not only of warehouseproducts but including warehouse raw materials, warehouseproduce, etc. So, the planning of layout and good warehousefacilities is required to movement of product could be faster orproduct can be distributed at the right time acccordance with theproduction target. The purpose of this research is to increaseproductivitiy and efficiency of the previous layout, and to know thedistance of material handling. Method used is shared storage thatserve to regulate and develop area-area based on the floor areawarehouse and also to sort placement area closets to exit withFIFO System (First In First Out). The result of this research iscapacity formerly only able to 648 pallet or 101.088 carton ofproducts, after conducted of planning the layout repeatedwarehouse can accommodate 720 pallet or 112.320 carton ofproducts, demand has an area of before was 567,39 m2 and after is417,81 m2, so it is more efficient, while for the distance of materialhandling before was 2935,65 m and after being set the repeated be2964,16, it is due to the amount of pallet more than before thanever so it takes distance of material handling larger.